Complementary enhanced solar thermal conversion performance of core-shell nanoparticles. (1st February 2018) - Chen, Meijie; He, Yurong; Wang, Xinzhi; Hu, Yanwei
Highlights: Optical properties of core-shell NPs were discussed systematically. Absorption efficiency can be adjusted by the core-shell or mixing ratios of NPs. Optimized parameters of the core-shell NPs for solar absorption were obtained. Efficiency of Au-decorated SiO2 NPs was superior to Au NPs and SiO2 NPs. Abstract: In this study, the properties of various types of core-shell nanoparticles (NPs) were evaluated using the finite difference time domain (FDTD) method towards the enhancement of solar absorption performance. Results showed that the resonance wavelength of SiO2 @Au NPs lay in the 540–900 nm range, covering the near-infrared and visible regions. The resonance wavelength of SiO2 @Ag NPs lay in the 390–830 nm range, covering the entire visible region. SiO2 @Au nanofluid with a core-shell ratio of φ  = 0.2 exhibited the highest solar absorption efficiency with 64% less Au consumption compared to pure Au NPs. For mixed nanofluids, the mixtures featuring core-shell ratios of 0.1 and 0.6 with mixing ratios of 0.5 for SiO2 @Au and 0.6 for SiO2 @Ag gave the highest absorption efficiencies. In addition, the peak solar absorption efficiency of a mixed nanofluid of SiO2 @Au ( φ  = 0.1) and SiO2 @Ag ( φ  = 0.4) with a mixing ratio of 0.58 was as high as 94.4%. Solar thermal conversion experiments revealed that, under the same conditions, a Au-decorated SiO2 nanofluid showed a comparable efficiency to the calculated solar absorption efficiency of the SiO2 @Au core-shell nanofluid (∼95.2%); it was as high as 95.9%, higher than those of Au NPs and SiO2 NPs. These results showed that adjusting the core-shell ratios and tuning the mixing ratios of different nanofluids are two efficient methods to enhance the solar absorption efficiencies of SiO2 @Au and SiO2 @Ag NPs under the optimal conditions.